Partition analysis to explore relationship between ABO blood group phenotypes and nCOVID-19 susceptibility – A retrospective observational study: Blood phenotypes and COVID-19 susceptibility - Bhandari, Sudhir; Shaktawat, Ajit Singh; Tak, Amit; Shukla, Jyotsna; Gupta, Jitendra; Patel, Bhoopendra; Kakkar, Shivankan; Dube, Amitabh; Dia, Sunita; Dia, Mahendra; Wehner, Todd C (Scripta Medica, 2020)
Background: Since the outbreak of coronavirus disease-19 (COVID-19) research has been continued to explore multiple facets of the disease. The objective of the present study was to evaluate the relationship between blood group phenotypes and COVID-19 susceptibility.Methods: In this retrospective observational study 132 hospitalised COVID-19 patients were enrolled from the Swai Man Singh (SMS) Medical Hospital in Jaipur, India after receiving approval from the Institutional ethics committee. The ABO, Rh and Kell blood group phenotypes along with demographic data of the patients were recorded. The observed proportions of ‘A’, ‘B’, ‘AB’, ‘O’, ‘Rh’ and ‘Kell’ blood groups in COVID-19 patients were compared against the expected proportions (the null hypothesis) of the general population using Pearson’s Chi-squared test and partition analysis.Results: There were significant differences between observed and expected frequency for the ABO and Kell blood phenotypes. Further partition analysis of ABO phenotypes showed that the group ‘A’ phenotypes were more susceptible to COVID-19. The Kell negatives were also more susceptible. The blood groups ‘AB’, ‘B’, ‘O’ and ‘Rh’ showed no significant difference for susceptibility to COVID-19.Conclusion: The study shows a relationship between ABO, Rh and Kell blood groups and COVID-19 susceptibility. The application of these relationships in clinics should be explored in future studies.
Keywords: ABO krve grupe; Osetljivost na COVID-19; Fenotipovi Kell krvnih grupa; Pearsonov Hi-kvadrat test; Rh fenotipovi krvnih grupa